11th International Conference of Sport Kinetics llalkidikj, Greece 25 - 27 September 2009 - Oleksandr, Krasilshchikov (Pusat Pengajian Sains Kesihatan, 2009)
Introduction. Osteoarthritis has been considered as one of the major health problems in the world (Eyigor, 2004). The physical disability arising from knee osteoarthritis prevents the performance of daily life activities such as walking, squatting and climbing stairs. Physical disability also has negatively affect patients' life quality (Sisto, 2006). Several factors cause the occurrence of physical disability including pain, limitation of joint movement, muscle weakness and coordination impairment (Diracoglu, 2005). Despite the well known fact that exercises are the effective treattnent in osteoarthritis, exact amount aod types of exercise that would be beneficial aod not destructive to the affected joint are unknown and most effective types and combinations of exercise as well as the amount are still unclear (Deyle et al., 2005). Methods. Sixteen middle aged women aged 50-64 years from among the patients diagnosed with knee osteoarthritis were recruited for the study and were randomly assigned to either intervention (n~8) or to the control group (n~8). Subjects were tested before and after 8 weeks of progressive combined training program, with three sessions a week frequency, in six minutes walking distance to measure the functional exercise capacity, WOMAC questionnaires to access pain symptoms aod patients' ability to perform daily activities and isokinetic testing with Biodex Isokinetic Dynamometer to access patients' knee peak torque. Results. Walking distance in intervention group has increased significantly by 14.3% (p<0.05) whereas it reduced by 3.4% in control group at post intervention tests. Pain scores were significaotly reduced by 44.1% in the intervention group (p<0.05), whereas they were increased by 48.8% in control group (p<O.Ol). The difference in pain score between control and experimental groups was statistically. significaot at the post test (p<O.OOl). Physical function scores were significaotly reduced by 55.0% in the intervention group (p<O.OOl) and increased by 30.5% in the control group (p<O.Ol). The difference in physical function score between groups was statistically significaot (p<O.OOl) in the post intervention testing. Right and left quadriceps muscles peak torque values at 120°/s and 180°/s angular velocities in intervention group at the post test have increased significantly. Peak torque value of right quadriceps muscle at 120°/s and 180°/s increased by 41.2% (p<O.Ol) and 32.2% (p <0.05) respectively. Peak torque of left quadriceps muscle at 120°/s and 180°/s increased by 103.7% (p<O.OOl) aod 30.8% (p<O.Ol) respectively. There were statistically significant differences in peak torque values of right and left quadriceps muscles at both aogular velocities between intervention and control groups after completion of the intervention program with obvious and statistically significant improvement in the intervention group in comparison to the control group. Discussion. Short-term training program combining flexibility, strength aod endurance activities in each session of eight weeks partially supervised exercises program lead to significaot improvements in quadriceps muscles peak torque, six minutes walking distance, pain and disability assessment in middle aged women with early stage primary knee osteoarthritis. Designed training programme is easily applicable, efficient, cost free and performable anywhere. It combines the positive effects of flexibility, strengthening and aerobic exercises in one exercise prescription programme.